Antibodies to Cardiolipin in Patients with Primary Biliary Cirrhosis - John Verrier Jones; Dianne P. Mosher; Edith Jones; C. Noel Williams; Dickran Malatjalian; Roland I. Carr; Mervat Mansour (Canadian Journal of Gastroenterology, 1989)
Antibodies to cardiolipin have been recognized in up to 65% of patients with systemic lupus erythematosus. It has been claimed that they are significantly associated with intravascular thrombosis and with obstetrical complications. Thus far they have been found to be less prevalent in other diseases. Because of the high concentration of cardiolipin in mitochondrial membranes and the presence of antimitochondrial antibodies in patients with primary biliary cirrhosis, the authors investigated the prevalence of antibodies to cardiolipin in a group of 31 patients with primary biliary cirrhosis. lt was found that the prevalence and levels of anticardiolipin antibodies of lgG and lgA isotype are as high in patients with primary biliary cirrhosis as in 35 consecutive patients with systemic lupus erythematosus. None of the patients with primary biliary cirrhosis gave any history of venous or arterial thrombosis. The rate of miscarriage was less than that reported for the general population. The availability for study of a second group of patients with high levels of anticardiolipin antibodies should make it possible to determine whether the association of these antibodies with thrombosis and fetal wastage in patients with systemic lupus erythematosus is a direct relation ship or an epiphenomenon.